Photograph Portrait - Ellwood Graham:::Creator::::::::::::
Photograph of a John Steinbeck portrait, done in the artists's studio on Huckleberry Hill soon after Steinbeck's return from Mexico.He thought having to sit for a portrait would force him to focus on writing the Sea of Cortez. Judith Deim worked on his portrait at the same time. This painting was done after Steinbeck rejected and refused to pay for Graham's initial effort (see 1-674). The painting was last known to have been owned by John Huston.